Hubungan antara lingkar dada, panjang dan tinggi badan dengan bobot badan kambing Senduro jantan - Wahyu Adhi Tama; Moch. Nasich; Sri Wahyuningsih (Faculty of Animal Science, Universitas Brawijaya, 2016)
This research was conducted in Senduro Sub-District, Lumajang from January 24th to February 24th 2016. The objective of the study was to determine the relationship between linear body measurement (chest girth (CG), body length (BL) and body height (BH)) and body weight of Senduro goats. The study used 104 Senduro goats that were categorized as PI0 to PI8. The correlation values between body weight and body measurements ranged from 0.90 to 0.97. The highest correlation values were found between body weight and chest girth (0.97, p<0.01). Correlation and regression analysis were applied to estimate the relationship among these traits. The study concluded that body weight had a strong correlation with chest girth (0.97), body length (0.92), and body height (0.90). Keywords: Senduro goat, body weight, chest girth, body length, body height